IMPROVING THE RESULTS OF LEARNING ‘CATHOLIC RELIGIOUS EDUCATION’ THROUGH THE IMPLEMENTATION OF THE STUDENT TEAMS ACHIEVMENT DIVISION TYPE COOPERATIVE MODEL (STAD) MAIN MATERIALS 'CHURCH SOCIAL TEACHING' IN CLASS XI IPS 1 SMAN 2 EAST KUPANG - Yulius Bera Tenawahang (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2021)
The purpose of this research is to improve the learning outcomes of